Strategi Transformasi Digital dalam Pemeriksaan Kualitas Air Bersih pada Laboratorium Kesehatan - Domi Sepri; Ahmad Fauzi (SEULANGA SYSTEM PUBLISHER, 2022)
The rapid development of information technology and the Industrial Revolution 4.0 has an impact on all lines of life, including the medical and health fields. The Ministry of Health has planned a digital transformation strategy in its blueprint planning document until 2024. One of the transformation strategies is about the health quality of clean water, because it is an important part in forming a healthy society. Sanitation health and clean water quality standards that have been set by the ministry of health in the process of being implemented by internal monitoring agencies, namely district/city health laboratories are generally still not digital-based. Health laboratories in general still carry out the registration service for the examination of clean water samples to the delivery of the results of labor examinations using paper records. It is prone to recording errors and is prone to loss. The process of digitizing the Clean Water Quality Inspection Information System was developed with a web-based application platform. This research is a Research and Development (R&D) research which was developed using the Process Flowchart Methodology or waterfalls. The flow of steps carried out is to analyze and build a design system and produce a system that becomes a recommendation in the process of transforming Information Technology-based services in the health sector for public services. So that this research can be used as a reference in the development of a digital transformation system